In vitro wear, corrosion and biocompatibility of electron beam melted γ-TiAl. (5th November 2017) - Mohammad, Ashfaq; Al-Ahmari, Abdulrahman M.; Balla, Vamsi Krishna; Das, Mitun; Datta, Susmit; Yadav, Devinder; Janaki Ram, G.D.
Abstract: Electron beam melting (EBM), a powder bed fusion based additive manufacturing process, has been used to fabricate Ti-48Al-2Cr-2Nb γ-TiAl samples. The samples were evaluated for their potential use in biomedical applications in terms of in vitro wear, corrosion and biocompatibility in as-deposited (AD) and hot isostatically pressed (HIPed) conditions. The samples were found to exhibit a lamellar microstructure consisting of γ-TiAl and Ti3 Al (α2 ) phases in both the conditions. However, their in vitro wear and corrosion performance in Hank's balanced salt solution (HBSS), with and without fetal bovine serum (FBS), was found to be very different. The AD samples exhibited comparable passive behavior to commercially pure titanium (CP-Ti). Their corrosion potentials and currents were better than those of CP-Ti. The γ-TiAl samples exhibited wear rates of the order of 10 − 4  mm 3 /N·m in HBSS. The presence of FBS was found to increase the corrosion and the wear rate of this alloy increased by 65%. In vitro cell culture experiments, using NIH3T3 cells, demonstrated that the EBM processed γ-TiAl is non-toxic and can allow cell adhesion and proliferation as effectively as CP-Ti. Graphical abstract: Highlights: The electron beam melted γ-TiAl alloy showed potential for use in biomedical implants. Hot isotatic pressing improved its in vitro corrosion resistance and cell viability (up to 42%). The alloy exhibited similar in vitro wear resistance in as-processed and hot isostatically pressed conditions. The presence of fetal bovine serum increased the wear rate of γ-TiAl alloy by 65%. Electron beam melted γ-TiAl is non-toxic and its cell-material interactions are comparable to that of titanium.